SMALL-SIDED GAMES IN FOOTBALL: EFFECT OF FIELD SIZES ON TECHNICAL PARAMETERS - Faruk Guven; Nurtekin Erkmen; Samet Aktas; Cengiz Taskin (Sport Scientific And Practical Aspects, 2025)
The aim of this study was to determine effects of field sizes on technical parameters of small-sided games in football players. Eight amateur football players (27.23 ± 3.08 years, heigth: 171.01 ± 5.36 cm, body weigth: 66.86± 4.54kg, sports experience: 12.88 ± 3.28 years) performed 4-a-side small-sided games (SSG) with different field sizes. In SSGs, field sizes were 30 x 40 m and 26 m x 24 m. SSGs was conducted as a series of 3 bouts of 6 min with 5 min recovery durations. All SSGs were videorecorded using two digital video camcorder positioned on a tripot. Shoot on taget, passes, succesful passes, unsuccesful passes, dripling, tackle, possession in SSGs were counted by Mathball Match Analysis System. The effects of bouts on technical score were examined separately using a Friedman’s test. Mann Whitney U test was applied to analyse differences between field sizes. There were no significant differences in shoots on target, total pass, successful pass, tackle, interception, possession between bouts in 30 x 40 m field size (p>0.05). Unsuccessful pass in bout 3 for 30 x 40 m field size was lower than bout 1 and bout 2 (p<0.05) and dripling in bout 3 was lower than bout 2 (p<0.05). There was no significant difference in technical actions between bouts for 26 x 34 m field size (p>0.05).Shoot on target in SSG with 26 x 34 m field size was higher than SSG with 30 x 40 m field size (p<0.05). unsuccessful pass for 26 x 34 m field size in bout 3 was higher than SSG with 30 x 40 m field size (p<0.05). There was no significant difference in technical actions between field sizes (p>0.05). In conclusion; in this study demonstrates that technical actions in a-4-side SSG are not influenced by different field sizes (for 30 x 40 m and 26 x 34 m field sizes). This consequence is same for both total SSG time and each bout. Dripling and unsuccessful pass decrease in bout 3 during SSG in 30 x 40 m field size.